Genetic Diversity and Distribution of Virulence-Associated Genes in Y. enterocolitica and Y. enterocolitica-Like Isolates from Humans and Animals in Poland - Katarzyna Morka; Ewa Wałecka-Zacharska; Justyna Schubert; Bartłomiej Dudek; Anna Woźniak-Biel; Maciej Kuczkowski; Alina Wieliczko; Jarosław Bystroń; Jacek Bania; Gabriela Bugla-Płoskońska (Pathogens, 2021)
Yersinia enterocolitica, widespread within domestic and wild-living animals, is a foodborne pathogen causing yersiniosis. The goal of this study was to assess a genetic similarity of Y. enterocolitica and Y. enterocolitica-like strains isolated from different hosts using Multiple Locus Variable-Number Tandem Repeat Analysis (MLVA) and Pulsed-Field Gel Electrophoresis (PFGE) methods, and analyze the prevalence of virulence genes using multiplex-Polymerase Chain Reaction (PCR) assays. Among 51 Yersinia sp. strains 20 virulotypes were determined. The most common virulence genes were ymoA, ureC, inv, myfA, and yst. Yersinia sp. strains had genes which may contribute to the bacterial invasion and colonization of the intestines as well as survival in serum. One wild boar Y. enterocolitica 1A strain possessed ail gene implying the possible pathogenicity of 1A biotype. Wild boar strains, represented mainly by 1A biotype, were not classified into the predominant Variable-Number Tandem Repeats (VNTR)/PFGE profile and virulotype. There was a clustering tendency among VNTR/PFGE profiles of pig origin, 4/O:3, and virulence profile. Pig and human strains formed the most related group, characterized by ~80% of genetic similarity what suggest the role of pigs as a potential source of infection for the pork consumers.